Internationalization: From concept to implementation - Craig Billingham; Monica Gragg; Guy Bentley (Laureate Education Inc, 2013)
Higher education is in a phase of rapid internationalization, with practices and impacts ranging from curriculum reform to satellite campuses to affiliated partner institutions. Internationally, higher education institutions are increasingly engaged with issues pertaining to technology integration. The primary reason for this is a growing acceptance of the importance of student-centered and heuristic learning, and the emergence of mobile devices as learning tools. The purpose of this case study is to describe and provide evidence for technology integration as an internationalizing practice that promotes and enables mobility for the brand, staff, and students of Blue Mountains International Hotel Management School (BMIHMS). This paper is also concerned to show technology integration as an internationalizing practice that promotes and enables brand, staff, and student mobility. In responding to the nascent trends in technology, and the continuing impacts globalization is having on higher education, BMIHMS has demonstrated that technology integration is an effective internationalizing practice. DOI: 10.18870/hlrc.v3i4.166